Dose response and kinetic analysis of thermoluminescence of Li–Zn fluoroborate glass. Issue 3 (3rd April 2017) - Thomas, Sunil; Chithambo, M. L.
ABSTRACT: The intention of this study is to explore the thermoluminescence properties of beta-irradiated Li–Zn fluoroborate glass. The glow-curve corresponding to 10 Gy shows two peaks when measured at 1°C/s. The dose response of the glass to beta irradiation was investigated. The trapping level parameters such as activation energy, frequency factor and order of kinetics associated with the observed glow-peak were determined using different methods. The thermoluminescence is affected by thermal quenching. A possible mechanism for the thermoluminescence is described.